Favourite Games Far from Denmark and The King's Volunteers on Amager - Simpson, Jane (Dance Books Ltd., Alton,Hampshire (UK), 2005)
Far from Denmark and The King's Volunteers on Amager. Edouard's a dreadful flirt, unable to keep his hand off any halfway pretty girl. PALABRAS CLAVE: Bournonville Festival, Royal Danish Ballet, Far from Denmark, The King's Volunteers on Amager
Dentro del apartado "August Bournonville. The Royal Danish Ballet hosts a birthday celebration".